The Holy See and the emergence of the modern Middle East : Benedict XV's diplomacy in Greater Syria (1914-1922) - Dreuzy, Agnes de (Washington, D.C. : The Catholic University of America Press, 2016)
"This detailed analysis of Pope Benedict XV's wartime diplomacy in the Levant focuses on relations between the Holy See and the European powers with Middle Eastern interests (France, Britain, and Russia) as well as the Ottoman Empire, and sheds new light on the intricate relationships between churches of the Eastern Rite (Maronites, Melkites) and those of the Latin Rite. The author argues that far from being passive and ineffectual during World War I, Benedict XV vigorously pursued a nuanced foreign policy that shaped the history of the papacy through the 20th century"--
Introduction : rethinking Benedict XV's contribution to international relations -- PART I. THE VATICAN AND CATHOLIC INTERESTS IN PREWAR AND WARTIME GREATER SYRIA, 1914-1917. Benedict XV, Pope of Peace -- Protection of Catholics in the Ottoman Empire -- Vatican wartime foreign policy -- Protection of Catholic clergy and property -- Benedict XV's humanitarian assistance -- PART II. POSTWAR PROTECTION OF CATHOLIC INTERESTS, 1917-1922. The Holy See and the postwar world order -- The Holy See and Syria -- The Holy See and Palestine -- Conclusion.
Print version record.
Includes bibliographical references and index.
Keywords: Catholic Church -- Foreign relations -- Middle East; Benedict -- XV, -- Pope, -- 1854-1922.; Benedict -- XV, -- Pope, -- 1854-1922.; Catholic Church; Middle East -- Foreign relations -- Catholic Church; Church and international organization -- Catholic Church -- History -- 20th century; World War, 1914-1918 -- Religious aspects -- Catholic Church; World War, 1914-1918 -- Peace -- History; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; Church and international organization -- Catholic Church; Diplomatic relations; International relations; Middle East; 1900-1999; Electronic books; History